Information Policy towards Stakeholders as a Manifestation of the Sustainable Development of the Insurance Market in Poland - Chmielowiec-Lewczuk, Magdalena; Nowak, Marta (Regional Barometer. Analyses & Prognoses, 2023)
The paper investigates the sustainability of the insurance market in Poland and its compliance with stakeholders’ requirements. Our objective is to assess the impact of sustainability principles on the insurance market in Poland. We apply the research method triangulation, including the quantitative and qualitative study. We find that most entities publish sustainability information. Insurance companies publish information mostly on climate, ecology, and the environment. However, this information is very different; in some cases, it is minimal and only follows regulations; in others, the scope is much broader. In most cases, this information is understandable for the readers, but, at this point, it is not comparable. The stakeholders require reliable data, mainly on the goals related to responsible production (goal no. 12 ), combating climate changes (goal no. 13 ), decent work (goal no. 8 ), sustainable industrialization and fostering innovation (goal no.9 ), life on land (goal no. 15 ), life under water (goal no. 14 ), and quality education (goal no. 4 ).